Dopamine D2 Receptor Occupancy Estimated From Plasma Concentrations of Four Different Antipsychotics and the Subjective Experience of Physical and Mental Well-Being in Schizophrenia: Results From the Randomized NeSSy Trial. Issue 6 (November 2019) - Veselinović, Tanja; Scharpenberg, Martin; Heinze, Martin; Cordes, Joachim; Mühlbauer, Bernd; Juckel, Georg; Rüther, Eckart; Paulzen, Michael; Haen, Ekkehard; Hiemke, Christoph; Timm, Jürgen; Gründer, Gerhard
Abstract: Background: Impaired subjective well-being in schizophrenia patients treated with antipsychotics has often been linked inter alia to the antidopaminergic effects of medication. Thus, it is important to capture the association between striatal dopamine D2 receptor occupancy (D2-RO) and global subjective well-being. We examined this association using data from our multicenter, randomized, double-blind Neuroleptic Strategy Study (NeSSy). Methods: An innovative double randomization process was used for allocation of patients to the specific treatment groups. Plasma drug concentrations were measured after 6 and 24 weeks of treatment to obtain the estimated D2-RO (eD2-RO) relative to literature values. We made an exploratory analysis of associations between eD2-RO and subjective well-being scores. One hundred two blood samples from 69 patients were available for the analysis. Because of the lack of a satisfactory occupancy model for quetiapine, only haloperidol, flupentixol, and olanzapine treatment groups were pooled, whereas aripiprazole data were analyzed separately, because of its partial agonistic properties. Results: In the pooled antagonist group, eD2-RO correlated negatively with the summarized well-being score. In a more detailed analysis, this association could be confirmed for all first-generation antipsychotic-treated patients, but not for the separate second-generation antipsychotic groups. In the aripiprazole group, higher eD2-RO was associated with impaired physical well-being, but had no association with mental well-being. Conclusions: Our results suggest that high plasma levels and consequently high occupancy at D2 receptors are disadvantageous for subjective well-being, as distinct from the objective extrapyramidal side effects. To minimize patients' malaise, which disfavors adherence, implementation of therapeutic drug monitoring in the clinical routine may be useful. Abstract : Supplemental digital content is available in the text.